World Report 2015 : Events of 2014 - Watch, Human Rights (Book collections on Project MUSE., 2015)
GeorgiaGuatemala; Guinea; Haiti; Honduras; India; Indonesia; Iran; Iraq; Israel/Palestine; Jordan; Kazakhstan; Kenya; Kuwait; Kyrgyzstan; Lebanon; Libya; Malaysia; Mali; Mexico; Morocco; Nepal; Nigeria; North Korea; Oman; Pakistan; Papua New Guinea; Peru; Philippines; Qatar; Russia; Rwanda; Saudi Arabia; Serbia; Kosovo; Singapore; Somalia; South Africa; South Sudan; Sri Lanka; Sudan; Syria; Tajikistan; Thailand; Tunisia; Turkey; Turkmenistan; Uganda; Ukraine; United Arab Emirates; United States; Uzbekistan; Venezuela; Vietnam; Yemen; Zimbabwe; 2014 HUMAN RIGHTS WATCH PUBLICATIONS.